Evolusi dan Inovasi Produk Tabungan Syariah di Indonesia : Analisis Kualitatif Berbasis Literatur - Rossa Amalia Lestari; Raihan Afif Kamal; Andi Amri (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This research aims to analyze the evolution and innovation of sharia savings products in Indonesia through a literature-based qualitative approach. The background of the research is based on the significant growth of the national sharia banking sector, driven by government regulations, technological advancements, and changes in customer preferences. This study uses a literature review method by analyzing various secondary sources such as scientific journals, regulations, and financial reports to identify the patterns of Islamic savings product development over time. The research results show that the transformation of sharia savings products is driven not only by religious aspects but also by the demand for service efficiency and financial inclusion. The merger of several Islamic banks into Bank Syariah Indonesia also accelerated the digitalization of Islamic savings services. Although there are challenges such as low Islamic financial literacy and limited infrastructure, development opportunities remain wide open through educational strategies and the integration of the halal ecosystem. Innovations such as the opening of online accounts and the diversification of goal-based products have successfully increased sharia financial inclusion, particularly among the younger generation. The implications of this research emphasize the importance of adaptive product development strategies, financial education, and cross-sector collaboration to strengthen the competitiveness and sustainability of sharia savings products in Indonesia.